Worldwide Landscape of Postal Financial Services : Asia Region - World Bank (Washington, DC, 2013)
Postal networks in the nine countries in the Asian region profiled here have 289,067 post offices. In many of these Asian countries, post offices have provided payments and savings services for more than 130 years. At the end of 2002, 335 million Asians had postal savings accounts, for a total balance of USD 83 billion (about 20 percent of the adult population). In China and Vietnam, postal savings have only been recently established, but are growing quickly. In addition to payment services, it provides domestic money transfers, including collecting bill payments. In some countries, e.g. Thailand, the role of postal networks in the payments system is significant. In general, however, transaction volumes for savings and payments together appear low, suggesting that many of these accounts may be dormant and may play only a marginal role in the payment system. Vigorous reform is required to develop intrinsically strong and competent institutions. The issue is not limited to repositioning postal financial services in the financial sector (instead of the public postal sector), the issue is also repositioning the postal network as the front-end of the financial sector and the modern information services (instead of the back office for mail processing, collection, and distribution). A vigorous approach will therefore have to include assessment of options, such as participation of and/or alliances with privately managed financial institutions, cross-border co-operation, private postal agents, and a process and approach not necessarily dependent on the pace and course of postal reform.